The Near Earth Asteroid associations - Jopek, Tadeusz (IAU Publisher: Cambridge Universtity Press, 2018)
We searched for associations (not for families) amongst the near Earth asteroids (NEAs) and, similarly as in our previous study (Jopek 2011, Jopek 2012), a dozen groups of 10 or more members was found with high statistical reliability. We present some details of our most numerous finding, association Anza ’2061’ which, at the moment, incorporates 191 members.
Keywords: Minor planets